2021
DOI: 10.33225/jbse/21.20.716
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Online Learning During the Covid19 Pandemic as Perceived by Engineering Education Students: A Multidimensional Model

Abstract: With the unprecedented crisis created by the Coronavirus pandemic, online teaching and learning became a global solution - embraced by the whole world - that tried to cover, at least in part, in part the problems encountered by the educational systems. An exclusively online format of teaching and learning proved to be a challenge for both the didactic and the learning process. Although the extant research during the pandemic is very abundant, there are few approaches addressing the different perceptions report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
3
0
2
Order By: Relevance
“…Educational efficiency decreases as distance education in departments where applied courses are intense and learning cannot be realized. In the study conducted by Gorghiu et al (2021), it was concluded that students have a lower perception of the usefulness of distance education due to the inability to carry out applied courses and laboratory studies.…”
Section: Discussionmentioning
confidence: 99%
“…Educational efficiency decreases as distance education in departments where applied courses are intense and learning cannot be realized. In the study conducted by Gorghiu et al (2021), it was concluded that students have a lower perception of the usefulness of distance education due to the inability to carry out applied courses and laboratory studies.…”
Section: Discussionmentioning
confidence: 99%
“…Учитељска и васпитачка професија је усмерена на рад са децом у различитим развојним стадијумима, када интелектуални, као ни биолошки развој још нису завршени, а учитељи и васпитачи имају улогу агенса социјализације и својом личношћу и знањем, директно или индиректно, могу утицати на процес формирања дечје личности и формирање самих црта личности, као релативно трајних диспозиција личности, које се манифестују у свакодневном понашању и функционисању појединца, што касније утиче и на само друштво у целини. Бројна истраживања указују да је овај проблем присутан код свих студената, без обзира на њихову будућу професију (Arroio, 2020;Asgari, Trajkovic, Rahmani, Zhang, Lo & Sciortino, 2021;Gorghiu, Pribeanu, Manea, Lamanauskas & Makarskaitė-Petkevičienė, 2021;Makamure & Tsakeni, 2020;Sepulveda-Eskobar & Morison 2020). Настава на даљину, која је на овај начин уведена Одлуком Владе Републике Србије, реализована је према програмима који су прилагођени условима њиховог извођења путем наставе на даљину, и то у кризној ситуацији пандемије нове инфективне болести COVID-19.…”
Section: табелаunclassified
“…Управо коришћење различитих платформи (поготову када је коришћена само једна платформа), може делимично да објасни и разлике у искуствима студенткиња са хитном наставом на даљину. Као разлог разноликој употреби средстава учења на даљину најчешће се наводи недовољна обученост наставника, у којој се начин комуникације и презентовања наставе одвија на оној платформи са чијим је функционисањем професор упознат, без обзира на то да ли то одговара студентима и самом предмету изучавања (Gorghiu et al, 2021;Singh-Pillay & Naidoo, 2020;Thakker, Parab & Kaisare, 2021). Ипак, треба напоменути да је доминантан вид извођења наставе асинхрон, без директног контакта уживо са студентима, који студентима омогућава вишекратни приступ у тренуцима када они то желе и/или могу, а не када је то прописано, што се може објаснити усклађивањем са обавезама у приватном животу наставника и студената и потпуном променом организовања живота и рада (Asgari et al, 2021;Ortiz Lovillo & Gidi Martí, 2021;Rahman, Rahman, Salamzadeh & Jantan, 2021;Singh-Pillay & Naidoo, 2020).…”
Section: дискусијаunclassified
See 1 more Smart Citation
“…When the studies on the subject in the related literature are examined, it was determined that hundreds of primary studies were done to determine the level of teachers' perceptions of distance education and technology use (Aldaghri & Oraif, 2022;Ali, 2020;Altinay, 2017;Amoozegar et al, 2018;Dalton, 2001;Elcicek, 2021;Elizabeth et al, 2020;Gorghiu et al, 2021;Hodges & Cullen, 2020;Kopcha, 2012;Makamure & Tsakeni, 2020;Makokotlela, 2022;Sadaf et al, 2016;Tilton & Hartnett, 2016;Tondeur et al, 2017;Wang, 2022;Yaylak, 2022). However, it was determined that the primary studies could not be synthesized and interpreted with a statistical result and a judgment could not be reached on whether they worked in practice or not.…”
Section: Introductionmentioning
confidence: 99%